2021
DOI: 10.1248/bpb.b21-00120
|View full text |Cite
|
Sign up to set email alerts
|

Pyoluteorin Induces Apoptosis and Autophagy in NSCLC Cells

Abstract: Pyoluteorin is a natural occurring antibiotic and its anti-tumor activity has rarely been reported. This study aims to investigate the anti-tumor effects of pyoluteorin on human non-small cell lung cancer (NSCLC) cells. The cell proliferation was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Apoptosis was determined through caspase3 activity assay and immunoblotting. Autophagy was measured by transmission electron microscope (TEM) and immunostaining. The autophagy-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…A similar study found that pyoluteorin inhibits Oomycetes, including Pythium ultimum , and contributes to the biocontrol of Pythium damping-off in cotton [ 26 ]. Pyoluteorin also has anti-tumor activity, which can induce cell cycle arrest and apoptosis in human triple-negative breast cancer cells [ 27 , 28 ]. Recently, pyoluteorin was reported to have activity against Chlamydomonas reinhardtii and Heterobasidion species [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study found that pyoluteorin inhibits Oomycetes, including Pythium ultimum , and contributes to the biocontrol of Pythium damping-off in cotton [ 26 ]. Pyoluteorin also has anti-tumor activity, which can induce cell cycle arrest and apoptosis in human triple-negative breast cancer cells [ 27 , 28 ]. Recently, pyoluteorin was reported to have activity against Chlamydomonas reinhardtii and Heterobasidion species [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the JNK/Bcl-2 pathway is blocked, the pyoluteorin-induced autophagy is significantly reduced. The combination of pyoluteorin with the autophagy inhibitor 3-MA significantly promotes human non-small cell lung cancer cell death and therefore can be considered as a potential anticancer strategy in lung cancer therapy [128]. Betulin is a naturally occurring pentacyclic triterpene with several pharmacologic effects, such as anti-inflammatory, antiosteoclastogenic, antiamnesic, and anticancer properties.…”
Section: Promotion Of Autophagy In Anticancer Therapymentioning
confidence: 99%
“…[13] Pyoluteorin could induce apoptosis and autophagy in non-small cell lung cancer. [14] Although destruction of proton gradients is known for pyoluteorin, no work has been done on its ability to bind to and inhibit proteins. Protein binding of the structurally similar pyrrolomycins, marinopyrroles, and armeniaspirols has been investigated, and they have been shown to inhibit a variety of different macromolecules (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pyoluteorin has been shown to have anti‐cancer effects via depolarization of mitochondrial membranes and accumulation of reactive oxygen species in triple negative breast cancer cells [13] . Pyoluteorin could induce apoptosis and autophagy in non‐small cell lung cancer [14] . Although destruction of proton gradients is known for pyoluteorin, no work has been done on its ability to bind to and inhibit proteins.…”
Section: Introductionmentioning
confidence: 99%